KREATIFITAS SENI MELIPAT HANDUK DI KAMAR HOTEL BERBINTANG - Anjas Hasbullah Komara; Yanti Nirmal (Eduturisma, 2018)
Towel art is one of hotel intangible services provided to guests as part of fulfilling excellentservice. This study aims to explain the various forms of towel art creativity and the makingprocess as well. The study was conducted using descriptive method with observation technique. The results of the study indicates that guests responded positively (both in impression and attitude) toward this service. The towel art manual guidance is stronglyneeded as ref